Secondary Towns and Poverty Reduction: Refocusing the Urbanization Agenda - Luc Christiaensen; Ravi Kanbur (Institute of Labor Economics (IZA), 2017)
This review is framed around the exploration of a central hypothesis: A shift in public investment towards secondary towns from big cities will improve poverty reduction performance. Of course the hypothesis raises many questions. What exactly is the dichotomy of secondary towns versus big cities? What is the evidence for the contribution of secondary towns versus cities to poverty reduction? What are the economic mechanisms for such a differential contribution and how does policy interact with them? We find preliminary evidence and arguments in support of our hypothesis, but the impacts of policy on poverty are quite complex even in simple settings, and the question of secondary towns and poverty reduction is an open area for research and policy analysis.
Keywords: I32; J61; O18; R12; R23; 330; secondary towns; poverty reduction; mega cities; urbanization; rural-urban migration; Zipf's Law